Reale Optionen und Landwirtschaftliche Betriebslehre - oder: Kann man mit der Optionspreistheorie arbitrieren? - Martin Odening; Oliver Musshoff (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2001)
– Real Options: Concept, Methods and Applicability in Agricultural EconomicsThis paper discusses the real options approach to investment. Real options facilitate an analysis of investment under uncertainty explicitly taking into account irreversibility of the investment decision and flexibility with respect to the investment timing. This is achieved by exploiting the analogy between a financial option and an investment project. We pinpoint the relation to traditional methods of capital budgeting as well as the special features of this concept, namely the exclusion of arbitrage opportunities and the independence of individual risk preferences. Analytical and numerical solution procedures for option pricing are presented. An application to investments in hog finishing illustrates the main ideas of the real options approach. It turns out that compared to traditional investment criteria, e.g. the net present value, the optimal investment trigger is considerably higher. Hence real options give an explanation for economic hysteresis. The reason for the increase of the investment trigger is that the opportunity to delay the investment decision, i.e. the value of waiting, causes opportunity costs that have to be covered by the expected investment returns. Finally model extensions, which consider different stochastic processes, compound real options, and competition, are discussed.
Keywords: 330; Landwirtschaftliche Betriebslehre; Betriebliche Investitionstheorie; Optionspreistheorie; Arbitrage Pricing; Schweinehaltung